Comment - Hansen, Alvin H. (Quarterly Journal of Economics, 1955)
Journal Article Professor Hansen and Keynesian Interest Theory: Comment Get access Alvin H. Hansen Alvin H. Hansen Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 69, Issue 4, November 1955, Pages 641–643, https://doi.org/10.2307/1882002 Published: 01 November 1955